Relationship between PM2.5 Dust Exposure and Exacerbation of Chronic Obstructive Pulmonary Disease Patients in Nan Hospital, Thailand - พิพัฒน์เวช, กนก; อุปจักร์, ศิริพร (Journal of Health Science of Thailand, 2021)
In the Northern Thailand, there are a lot of forest burnings that causes air pollution. Exposure to ambient particles with median aerodynamic diameter less than 2.5 µm (PM2.5) is found to be a risk factor that caused acute exacerbation of chronic obstructive pulmonary disease (AECOPD). But the research studies on PM2.5 correlations with the recurrence of COPD in northern Thailand are rare. The objective of this study was to assess the relationship between the duration and amount of exposure to PM2.5 and the relapse as well as the hospitalization in COPD patients. It was conducted as a cross-sectional study (prospective data collection) during January 2019 to May 2019 in COPD patients aged over 40 years who came for treatment at Nan Hospital, Thailand. Data on the general characteristics of the COPD patients were collected, including age, gender, occupation, education, smoking behavior and their hometown. Factors affecting the occurrence of AECOPD were also collected which included PM2.5 levels and the duration of exposure before coming to the hospital. Data were analyzed by using by multiple logistic regression. There were 851 COPD patients with AECOPD and 1,351 cases without exacerbation. For the AECOPD cases, 63.0% were male and 93.7% aged over 60 years old. The average age of patients in the study was 74.7+9.6 years. Factors affecting the occurrence of acute exacerbation of COPD were 2.4 times more smoking history. Receiving PM2.5 36-75 µg/m3 and PM2.5 exposure greater than 75 µg/ m3 . COPD prevalence was significantly associated with elevated PM concentration levels: adjusted OR 1.5 for more than 35 µg/m3 and less than 75 µg/m3 and adjusted OR 1.6 for more than 75 µg/m3 . Exposure to PM2.5 levels 36-75 µg/m3 increased the exacerbation of chronic obstructive pulmonary disease by 1.3 times, and exposure to PM2.5 levels greater than 75 µg/m3 increased the relapse of chronic obstructive pulmonary disease by 1.4 times. The recurrence of COPD was also found to be associated with the exposure at high concentrations of PM2.5 greater than 75 µg/m3 within one to four days. Physicians should recommend the practice of self care in such patients during the period of high pollution to prevent relapse.